Too Many Resources or Too Few? What Drives International Conflicts? - Georg Strüver (German Institute of Global and Area Studies (GIGA), 2010)
International conflicts over natural resources are frequently cited as the most prominent threat to global peace in the decades ahead. However, this subject has not yet been adequately tackled in the academic literature. This paper contributes to filling the gap by, first, proposing a four-class typology of resource conflicts and by, second, testing these conflict types against data on fossil fuels and interstate conflicts derived from two major conflict datasets: the Militarized Interstate Dispute Dataset (1960-2001) and the UCDP/PRIO Armed Conflicts Dataset (1960-2008). The findings, although preliminary, suggest that resource scarcity may play a less prominent role in the aggression of belligerent countries than is often assumed and that the existence of large oil deposits and high resource-rent incomes are better predictors of conflict involvement. – – Internationale Konflikte um natürliche Ressourcen werden als eine wesentliche Bedrohung für den internationalen Frieden in den kommenden Jahrzehnten angesehen. Das Thema wurde in der akademischen Literatur bisher jedoch nur unzulänglich behandelt. Das vorliegende Arbeitspapier trägt zum Schließen dieser Forschungslücke bei, indem erstens die Unterscheidung von vier Ressourcenkonflikttypen vorgeschlagen und zweitens die Existenz der verschiedenen Konflikttypen anhand von Ressourcendaten und zwei Konfliktdatenbanken, den 'Militarized Interstate Disputes'-Daten (1960-2001) und dem 'UCDP/PRIO Armed Conflicts Dataset' (1960-2008), empirisch geprüft werden. Erste Ergebnisse zeigen, dass sich die Teilnahme an internationalen Konflikten besser durch umfangreiche Rohstoffvorkommen und die Verfügbarkeit beträchtlicher Einnahmen aus dem Ressourcensektor in den kriegführenden Staaten vorhersagen lässt. Die Bedeutung von Ressourcenarmut ist geringer zu bewerten, als weitläufig angenommen wird.
Keywords: 300; resource scarcity; resource abundance; interstate conflicts; military intervention; Rohstoffressourcen; Politischer Konflikt; Welt